Use of EchoNavigator, a novel echocardiography-fluoroscopy overlay system, for transseptal puncture and left atrial appendage occlusion - Gafoor, Sameer; Franke, Jennifer (Journal of interventional cardiology, 2015)
Structural heart disease requires a coordinated effort to join echocardiographic and fluoroscopic data. Various methods have been used, including echocardiography, CT, and MRI. We report on the use of EchoNavigator (Philips Inc., Amsterdam, Netherlands), a novel echocardiographic-fluoroscopic fusion system. This new system allows real-time integration and marking of important structures that track on fluoroscopy even with movement of the C-arm. In this article, we describe potential uses for this system in respect to transseptal puncture and left atrial appendage closure.
Gesehen am 06.08.2021